Diversity Status of Arbuscular Mycorrhizal (AM) Fungi from Rhizospheric Soils of Medicinal and Aromatic Plants in Himachal Pradesh - Chandel, Sunita (Indian Forester, 2016)
Arbuscular mycorrhizal (AM) fungi are known to improve plant growth, nutrition uptake and defense mechanisms in plants. AM fungi have been observed to be associated with many plants including medicinal and aromatic plants. In the present study an attempt was made to study the diversity status of the AM fungi associated with medicinal and aromatic plants, Himachal Pradesh, India. It was noticed that the AM fungal spores were invariably present in the rhizospheres of all plants screened except Cichorium intybus, Saussurea lappa, Gentiana kurroo, Spilanthus acemella and Withania somnifera. Maximum number of AM fungal spores was recorded from soil samples collected from Solan district followed by Sirmour, Kinnaur and Mandi districts. Among different soil samples analysed, Solanum laciniatum harbours maximum AM fungal spores followed by Alpinia calcarata, Roscoea alpinia in Solan. A total of four different genera of AM fungi viz., Acaulospora, Glomus, Entrophospora and Scutellospora were isolated and identified. Among them, the genus Glomus was found dominant with maximum frequency percentage occurrence (80%) when compared to other genera.